Thermal niches are more conserved at cold than warm limits in arctic‐alpine plant species - Loïc Pellissier; Kari Anne Bråthen; Pascal Vittoz; Nigel G. Yoccoz; Anne Dubuis; Eliane S. Meier; Niklaus E. Zimmermann; Christophe F. Randin; Wilfried Thuiller; Luc Garraud; Jérémie Van Es; Antoine Guisan (Global Ecology and Biogeography, 2013)
Aim Understanding the stability of realized niches is crucial for predicting the responses of species to climate change. One approach is to evaluate the niche differences of populations of the same species that occupy regions that are geographically disconnected. Here, we assess niche conservatism along thermal gradients for 26 plant species with a disjunct distribution between the A lps and the A rctic. Location E uropean A lps and N orwegian F innmark. Methods We collected a comprehensive dataset of 26 arctic‐alpine plant occurrences in two regions. We assessed niche conservatism through a multispecies comparison and analysed species rankings at cold and warm thermal limits along two distinct gradients corresponding to (1) air temperatures at 2 m above ground level and (2) elevation distances to the tree line ( TLD ) for the two regions. We assessed whether observed relationships were close to those predicted under thermal limit conservatism. Results We found a weak similarity in species ranking at the warm thermal limits. The range of warm thermal limits for the 26 species was much larger in the Alps than in Finnmark. We found a stronger similarity in species ranking and correspondence at the cold thermal limit along the gradients of 2‐m temperature and TLD . Yet along the 2‐m temperature gradient the cold thermal limits of species in the Alps were lower on average than those in Finnmark. Main conclusion We found low conservatism of the warm thermal limits but a stronger conservatism of the cold thermal limits. We suggest that biotic interactions at the warm thermal limit are likely to modulate species responses more strongly than at the cold limit. The differing biotic context between the two regions is probably responsible for the observed differences in realized niches.